“It Just Messes Your Mind”: U.S. International Students’ Perspectives of and Experiences with Academic Text Sourcing - Isbell, Janet Kesterson; Chaudhuri, Jayati; Schaeffer, Deborah L. (Journal of International Students, 2018)
This critical case study explored how six international students enrolled in two U.S. universities perceived and understood the concept of plagiarism. Through our participants’ stories, we challenged a system that insists on international students’ conformity, without adequate knowledge or training, to a U.S. or Western system of text borrowing and sourcing that may be different from what the students have learned in their home countries. Our study calls for educational rather than punitive means of addressing international students’ problems with crediting sources.